2021
DOI: 10.1002/jid.3541
|View full text |Cite
|
Sign up to set email alerts
|

Financing the economy: The multidimensional influences of financial development on economic complexity

Abstract: This study examines how financial development influences economic complexity, using a broad index of financial development. By utilising a global sample of 86 countries over the period 2002-2017 and applying several econometric techniques, we find that financial institutions and financial markets, as well as their sub-indices (financial depth, financial access and financial efficiency), have significantly positive impacts on economic complexity. Interestingly, financial institutions have a stronger effect than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 80 publications
4
27
0
1
Order By: Relevance
“…);Daude et al (2016);Kurt (2018);Lapatinas (2019);Şahin & Durmuş (2020);Şeker & Şimdi (2019);Şeker (2019);Uçar et al (2019), andKhan et al (2020). The findings regarding the direct causal effect that financial development imposes on economic complexity confirm the results inCan & Doğan (2018);Chu (2020);Kurt & Azazi (2018);Nguyen et al (2020);Nguyen & Su (2021);Şahin & Durmuş (2020). Lastly, bi-directional causalities between globalization and financialization and between economic globalization and financial development partially confirm the results ofKandil et al (2015);Law et al (2014);Muye & Muye (2017).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…);Daude et al (2016);Kurt (2018);Lapatinas (2019);Şahin & Durmuş (2020);Şeker & Şimdi (2019);Şeker (2019);Uçar et al (2019), andKhan et al (2020). The findings regarding the direct causal effect that financial development imposes on economic complexity confirm the results inCan & Doğan (2018);Chu (2020);Kurt & Azazi (2018);Nguyen et al (2020);Nguyen & Su (2021);Şahin & Durmuş (2020). Lastly, bi-directional causalities between globalization and financialization and between economic globalization and financial development partially confirm the results ofKandil et al (2015);Law et al (2014);Muye & Muye (2017).…”
supporting
confidence: 69%
“…Similarly, Chu (2020) empirically examined the impacts of developments in the banking sector and the stock market on economic sophistication and showed that both financial development indicators increase product sophistication in a sample of 94 countries. Additionally, Nguyen & Su (2021) verified that financial development leads to increases in economic complexity in a selection of 86 countries. Lastly, for a panel of 120 countries, Yu & Qayyum (2021) studied how financial openness affects economic complexity.…”
Section: The Economic Complexity-financial Development Linkmentioning
confidence: 91%
See 1 more Smart Citation
“…Активизировалась разработка технологических платформ как инструментов для совместной работы по максимизации потребительской ценности и удовлетворения запросов клиентов. Перечисленные процессы находятся под влиянием растущей экономической сложности, которая наблюдается в странах как с высоким, так и низким уровнем дохода (Nguyen et al, 2020;Nguyen, Su, 2021).…”
Section: банки во время кризисаunclassified
“…The primary benefit of these indices is their multi-dimensional approach to financial development, which is defined by a combination of financial institutions and market depth, access, and efficiency. Since the IMF calculated and published them, various authors who studied financial development have resorted to them and used them in their studies-see, for example, Laktionova et al (2021), Islam et al (2020), Mignamissi (2021), Ejemeyovwi et al (2021), Su (2021), andBaloch et al (2021). Of these indexes, we have alternatively used in the model the broader Financial Development Index (FDI), but also its two main components-Financial Institutions Index (FII) and Financial Markets Index (FMI)-each capturing financial institutions and markets particularities.…”
Section: Data and Data Sourcesmentioning
confidence: 99%